Purification method of electronic grade trimellitic anhydride

By purifying trimellitic anhydride using high-strength film separation materials, the problems of low purity, large energy consumption and complex operation in the prior art are solved, and the high-efficiency, simple and low-cost purification effect of high-purity trimellitic anhydride is achieved.

CN119701635APending Publication Date: 2025-03-28JIANGSU ZHENGDAN CHEM IND CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411880624.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing trimellitic anhydride purification method has the disadvantages of low purity, large energy consumption, and complex operation, and it is difficult to meet the demand for high-purity chemicals of electronic materials.

Method used

Trimellitic anhydride is purified by using high-strength film separation material. By preparing crystal structures with nanopores and surface metal coating modification, the film material has excellent separation performance and mechanical strength.

Benefits of technology

It realizes efficient purification of trimellitic anhydride, ensuring high purity, and has the advantages of simple operation, low cost and environmentally friendly, and is suitable for large-scale industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005198116440000071
    Figure BDA0005198116440000071
  • Figure BDA0005198116440000081
    Figure BDA0005198116440000081
  • Figure BDA0005198116440000082
    Figure BDA0005198116440000082
Patent Text Reader

Abstract

The invention relates to a method for purifying electronic grade trimellitic anhydride in the technical field of new materials, which comprises the following steps of: preparing a substrate mixture, arranging a metal nanoparticle polyester coating material outside a high-strength membrane separation material in a mold, sintering and annealing to obtain a metal particle reinforced high-strength membrane separation material Zn / Ti (at) SMC-Y1, the trimellitic acid semi-finished product batch material passes through a filtering device filled with Zn / Ti (at) SMC-Y1, the filtering device is provided with a high-pressure backflushing device filled with nitrogen and pure water, when the membrane flux is low, the trimellitic acid semi-finished product batch material is used for purging stacked solids, and after the membrane is regenerated, filtering is conducted again till the maximum purification precision is achieved; and putting the purified trimellitic acid into a dehydration anhydride forming device for dehydration to obtain trimellitic anhydride. The method can realize efficient purification on the premise of ensuring high purity, and has the advantages of simplicity and convenience in operation, low cost, environmental friendliness and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for purifying trimellitic anhydride in the technical field of new materials, in particular to a method for purifying electronic-grade trimellitic anhydride. Background Art

[0002] Trimellitic anhydride, 1,2,4-benzenetricarboxylic anhydride, referred to as trimellitic anhydride or TMA. It is a white or slightly colored flake solid and is an important fine chemical raw material. TMA molecules contain two functional group structures, anhydride and carboxyl, which make it have the chemical properties of anhydride and aromatic carboxylic acid. It is an important organic synthetic raw material and polyester monomer. At present, trimellitic anhydride is mainly used in the production of plasticizers, advanced powder coatings, insulating materials, and high-temperature curing agents for epoxy resins for polyvinyl chloride (PVC) resins. In the preparation process of electronic materials, the demand for high-purity chemicals is increasing. As an important electronic material intermediate, the purity of trimellitic anhydride directly affects the performance of the final product.

[0003] CN102516212A provides a method for reducing the impurity content in trimellitic anhydride. By using a fin-type melting crystallizer, using heat transfer oil to control the temperature rise and fall of the crystallizer tube shell layer, first gradually reducing the temperature of the tube side heat transfer oil in the shell layer, so that the trimellitic anhydride is crystallized in the shell side, and then after the liquid rich in low melting point impurities that has not yet been crystallized is discharged, the temperature of the tube side heat transfer oil is gradually increased to gradually melt the trimellitic anhydride, so that the high melting point impurities and the remaining part of phthalic anhydride are sublimated and adhered to the inner surface of the top cover of the melting crystallizer, and then the top cover of the melting crystallizer is replaced; the valve at the bottom of the melting crystallizer is opened to allow the molten trimellitic anhydride finished product to flow out; the temperature is increased again to fully melt the trimellitic anhydride, temporarily store it in an intermediate tank, and finally purify it by alcohol washing.

[0004] CN112110813A discloses a method for promoting the crystallization of trimellitic acid and thus increasing its content. The method adopts a multi-stage crystallization mode during crystallization, introduces air or oxygen-rich gas during the first stage of crystallization, causes the trimellitic acid oxidation product in the trimellitic acid oxidation reactor to continue to undergo oxidation reaction in the first crystallizer, thereby making the reaction more complete and reducing impurities. At the same time, under the turbulent action of the gas, the impurities are separated from the trimellitic acid, and the material coming out of the first crystallizer enters the subsequent crystallizer for further crystallization, thereby obtaining trimellitic acid crystals with less impurities and a particle size of more than 70 μm.

[0005] The shortcomings of the prior art are that traditional purification methods such as distillation and recrystallization often have the disadvantages of low purity, high energy consumption, and complex operation. Summary of the invention

[0006] The purpose of the present invention is to provide a method for purifying electronic grade trimellitic anhydride, which first prepares a high-strength membrane separation material, then uses the high-strength membrane separation material to purify trimellitic acid, and finally dehydrates it into anhydride to obtain trimellitic anhydride. The method can achieve efficient purification under the premise of ensuring high purity and has the advantages of simple operation, low cost, environmental friendliness, etc.

[0007] The present invention achieves the above object by the following steps: A method for purifying electronic grade trimellitic anhydride comprises the following steps:

[0008] (1) Preparation of base mixture

[0009] Silicon dioxide, molybdenum oxide and single crystal silicon are pre-ball-milled, cooled, and then activated carbon is added and calcined at high temperature in air, so that silicon dioxide, molybdenum oxide and single crystal silicon and activated carbon are crystallized at high temperature to form a crystal structure with nanopores. After the calcination, they are then calcined in air with an open flame to remove surface impurities and change the surface from black to grayish white, thereby obtaining Si-Mo / C particles, which are recorded as SMC particles.

[0010] Then SMC particles, attapulgite, diatomaceous earth, magnesium oxide, 45 # The steel powder and the rare earth yttrium powder are mixed and ball-milled, and then vacuum ball-milled, and after the ball mill is cooled, a matrix powder is obtained;

[0011] Then, the base powder is dissolved in triethylamine and dispersed evenly, polyvinylidene fluoride, polyethyl methacrylate, polyethylene glycol and trioctyl trimellitate or tetraoctyl pyromellitate are added, stirred thoroughly, and dried to obtain a base mixture;

[0012] (3) Preparation of Metal Nanoparticle Polyester Coating Materials

[0013] Prepare an ethanol solution of γ-methacryloxypropyltrimethoxysilane (KH-570), add dimethylformamide as a stabilizer, mix well and set aside;

[0014] Then, ZnO powder and tetraisopropyl titanate are weighed in proportion and dissolved in deionized water, and azobisisobutyronitrile is added dropwise and nitrogen is sealed. After heating in a water bath and stirring, KH-570 ethanol solution is added dropwise. After the reaction is complete, glacial acetic acid or ammonia water is added dropwise to adjust the solution to neutrality, and the mixed liquid is then uniformly mixed with polyester resin to obtain a metal nanoparticle polyester coating material, which is sealed for later use;

[0015] (3) Preparation of high-strength membrane separation materials reinforced with metal particles

[0016] A mixture of hydroxyethyl methacrylate (HEMA) and the metal nanoparticle polyester coating material obtained in step (2) in a mass ratio of 1: (0.5-1.2) is evenly applied on the surface of the film mold, and then the base mixture obtained in step (1) is filled into the mold, and after pressure compaction, a temperature rise program is set to sinter and form, and after cooling, annealing treatment is performed, and demolding is performed at room temperature by natural cooling, immersing in a water bath for rinsing and then drying to obtain a metal particle reinforced high-strength composite film, which is recorded as Zn / Ti@SMC-Y1;

[0017] (4) Purification of trimellitic anhydride

[0018] A high-strength composite membrane reinforced with metal particles is installed in a filtering device and used as a filter material. The filtering device is also equipped with a high-pressure recoil device for nitrogen and pure water. When purifying trimellitic acid, a batch of semi-finished trimellitic acid products is filtered through the filtering device using intermittent operation. When the membrane flux decreases below an ideal value, the high-strength composite membrane reinforced with metal particles is regenerated by high-pressure recoil of nitrogen and pure water. After regeneration, filtration is continued until the trimellitic acid reaches a maximum purification accuracy. The purified trimellitic acid is placed in a dehydration anhydride dehydrator for dehydration to obtain trimellitic anhydride.

[0019] In the step (1), the mass ratio of silicon dioxide, molybdenum oxide, single crystal silicon and activated carbon is (25-30): (0.5-2): (8-13): 35, and the ball milling time is 2 hours; the calcination temperature is 400-600° C., and the calcination time is 4-5 hours.

[0020] The mass ratio of the SMC particles, attapulgite, diatomaceous earth, magnesium oxide, 45# steel powder and rare earth yttrium powder in the step (1) is (10-15): (60-100): (80-150): (20-40) (30-45): (0.5-1), and the ball milling time is 2 hours.

[0021] The mass ratio of the base powder and triethylamine in step (1) is 2:5; the volume ratio of the polyvinylidene fluoride, polyethyl methacrylate, polyethylene glycol and trioctyl trimellitate or tetraoctyl pyromellitate is 5:2:1:(10-12), wherein trioctyl trimellitate and tetraoctyl pyromellitate can be used in an equal volume to replace each other.

[0022] In step (2), the amount of ethanol used is 20 to 30 times the mass amount of KH-570, the amount of dimethylamide used is 1 to 3 times the mass amount of KH-570, the mass ratio of ZnO powder and tetraisopropyl titanate is (1 to 2): 5; the amount of azobisisobutyronitrile added is 0.3% of the total mass of the aqueous solution of ZnO powder and tetraisopropyl titanate; the constant temperature of the water bath is 30 to 45° C., and the stirring time is 5 to 6 hours; the amount of the polyester resin used is 10 to 15 times that of the mixed liquid.

[0023] In step (3), the mold pressure is 20-30 MPa; the sintering process is vacuum sintering, the vacuum degree is 8-15 Pa, the heating rate is 30-45°C / min, the sintering temperature is 1000-1500°C; the annealing temperature is 400-600°C, and the holding time is 2-3 hours. The water bath rinsing temperature is 20°C, and the rinsing time is 1-3 hours.

[0024] The aqueous solution after high-pressure backwashing in step (4) can be circulated into the raw material kettle for repeated filtration, which can improve the utilization rate of the raw materials.

[0025] In the above technical scheme, the SMC particles and rare earth yttrium powder act as modified particle monomers; the metal nanoparticle polyester acts as a surface modifier of the composite film; attapulgite, diatomaceous earth and 45# steel powder serve as molding agents and structural monomers of the composite film; trioctyl trimellitate or tetraoctyl pyromellitate serves as a binder of the composite film; polyethyl methacrylate and polyethylene glycol serve as pore-forming agents of the composite film; and magnesium oxide serves as a sintering aid of the composite film.

[0026] Compared with the prior art, the present invention has the following advantages:

[0027] 1. The membrane separation material prepared by the present invention has excellent separation performance and mechanical strength, and can ensure long-term stable operation of the membrane material while achieving efficient purification.

[0028] 2. The present invention adopts the tempered modification of inorganic non-metallic membrane materials, utilizes nano-scale hollow tubular attapulgite as the structural monomer, and introduces rigid powder materials, SMC nanoparticles and rare earth metal particles to make the internal structure of the membrane material more stable, thereby ensuring that the pore structure of the membrane material is not destroyed during high-pressure recoil and the separation accuracy is higher.

[0029] 3. The present invention modifies the surface metal coating so that the surface of the membrane material is not easily corroded and the precipitated solid particles are not easily adhered to the surface of the membrane material. The introduction of silane coupling agent into the polyester coating can make the coating more firm and the metal particles of the coating are not easy to fall off.

[0030] 4. The preparation method of the membrane material of the present invention is simple and convenient, and the purification operation is convenient. It is low-cost, environmentally friendly, suitable for large-scale industrial applications, and can significantly improve the purity of trimellitic anhydride to meet the demand for high-purity chemicals for electronic materials.

[0031] Compared with the prior art, the present invention has the following advantages:

[0032] (1) The membrane separation material prepared by the sol-gel method, metal plating method and calcination molding method of the present invention has excellent separation performance and mechanical strength, and can ensure long-term stable operation of the membrane material while achieving efficient purification.

[0033] (2) The present invention adopts the tempered modification of inorganic non-metallic membrane materials, uses nano-scale hollow tubular attapulgite as the structural monomer, and introduces rigid powder materials, SMC nanoparticles and rare earth metal particles to make the internal structure of the membrane material more stable, thereby ensuring that the pore structure of the membrane material is not destroyed during high-pressure recoil and the separation accuracy is higher.

[0034] (3) The present invention modifies the surface metal coating so that the surface of the membrane material is not easily corroded and the precipitated solid particles are not easily adhered to the surface of the membrane material. The introduction of silane coupling agent into the polyester coating can make the coating more solid and the metal particles of the coating are not easily fallen off.

[0035] (4) The preparation method of the membrane material of the present invention is simple. It only needs to evenly apply the precursor solution on the surface of the substrate, and after gelation and drying, calcination and molding are performed to obtain a high-performance membrane. During the purification operation, the impurities can be removed by filtering the trimellitic anhydride solution through a membrane to achieve the preparation of high-purity trimellitic anhydride. The method is low-cost, environmentally friendly, suitable for large-scale industrial applications, and can significantly improve the purity of trimellitic anhydride, meeting the demand for high-purity chemicals for electronic materials. DETAILED DESCRIPTION

[0036] Example 1

[0037] A method for purifying electronic grade trimellitic anhydride is carried out according to the following steps:

[0038] (1) Preparation of base mixture

[0039] First, 50g of silicon dioxide, 2g of molybdenum oxide and 11g of single crystal silicon were pre-ball milled for 2h, and then 70g of activated carbon was added after cooling, and calcined at 550℃ in a muffle furnace for 4h. After the reaction was completed, it was roasted in air until it was fixed to obtain Si-Mo / C particles (referred to as SMC particles). Then 15g of SMC particles, 80g of attapulgite, 100g of diatomaceous earth, 30g of magnesium oxide, 40g of 45# steel powder and 0.5g of rare earth yttrium powder were weighed respectively, and after stirring and mixing evenly, vacuum ball milled for 2h, and after the ball mill was cooled, the matrix powder was obtained. Then the matrix powder was dissolved in triethylamine and dispersed evenly, 50mL of polyvinylidene fluoride, 20mL of polyethyl methacrylate, 10mL of polyethylene glycol and 120mL of trioctyl trimellitate or tetraoctyl pyromellitate were added and stirred until slurry, and the base mixture was obtained after being taken out and dried.

[0040] (2) Preparation of Metal Nanoparticle Polyester Coating Materials

[0041] First, prepare 500mL of 5% (v / v) γ-methacryloxypropyltrimethoxysilane (KH-570) ethanol solution, add 30mL of dimethylformamide as a stabilizer, mix well and set aside. Then weigh 10g of ZnO powder and 50g of tetraisopropyl titanate and dissolve them in 250mL of deionized water, add 0.5mL of azobisisobutyronitrile, seal with nitrogen and stir in a 40℃ water bath for 5h. Then add KH-570 ethanol solution, and after the reaction is complete, add glacial acetic acid or ammonia water to adjust the solution to neutrality. The obtained surface modifier is evenly mixed in polyester resin and sealed and stored at low temperature.

[0042] (3) Preparation of high-strength membrane separation materials reinforced with metal particles

[0043] Hydroxyethyl methacrylate (HEMA) and the metal nanoparticle polyester coating are evenly applied in equal proportions on the surface of the film mold. After natural drying, the base mixture obtained in step (1) is filled into the mold and pressed to compact it. The pressing pressure is 20-30 MPa, and then vacuum sintering is performed. The vacuum degree is 8-15 Pa, the heating rate is 30-45°C / min, and the sintering temperature is 1000-1500°C. Annealing is then performed at a temperature of 400-600°C and a holding time of 2-3 hours. After that, the film is naturally cooled and demolded at room temperature. The obtained film material is immersed in a 20°C water bath for rinsing for 2 hours and then dried to obtain a high-strength film reinforced with metal particles, which is recorded as Zn / Ti@SMC-Y1.

[0044] (4) Purification of trimellitic anhydride

[0045] A high-strength composite membrane reinforced with metal particles is installed in a filtering device and used as a filter material. The filtering device is also equipped with a high-pressure recoil device for nitrogen and pure water. When purifying trimellitic acid, a batch of semi-finished trimellitic acid products is filtered through the filtering device using intermittent operation. When the membrane flux decreases below an ideal value, the high-strength composite membrane reinforced with metal particles is regenerated by high-pressure recoil of nitrogen and pure water. After regeneration, filtration is continued until the trimellitic acid reaches a maximum purification accuracy. The purified trimellitic acid is placed in a dehydration anhydride dehydrator for dehydration to obtain trimellitic anhydride.

[0046] The prepared composite membrane is loaded into the membrane filtration equipment, pressed with a sealing ring and loaded into the membrane filter and kept wet at 2.0Mpa for 1 hour. Take 20kg batch material and store it in the liquid collecting tank of the membrane filter. The batch material is controlled by the solenoid valve to enter the interior of the composite membrane through the tube layer at 10mL / min. The acetic acid solution containing impurities is discharged from the shell layer. When the membrane flux is lower than 5LMH or after half an hour of operation, the trimellitic acid solid accumulated in the tube body is backwashed with nitrogen and pure water at high pressure, and the batch material is tested for liquid phase concentration every 30 minutes. After purification for 5-6 hours, the high-purity trimellitic acid is placed in the dehydration anhydride to obtain electronic grade trimellitic anhydride (the content of trimellitic acid is equivalent to the content of trimellitic anhydride).

[0047] Comparative Example 1

[0048] On the basis of step (1) of Example 1, the base mixture is directly filled into a membrane mold, compacted at a pressure of 20 to 30 MPa, and then vacuum sintered at a vacuum degree of 8 to 15 Pa, a heating rate of 30 to 45°C / min, and a sintering temperature of 1000 to 1500°C; then annealed at a temperature of 400 to 600°C for 2 to 3 hours, and then naturally cooled and demolded at room temperature to obtain a high-strength composite membrane without metal particle reinforcement, which is recorded as SMC-Y1.

[0049] Comparative Example 2

[0050] Preparation of membrane separation material (SMC-Y2)

[0051] Silicon carbide, diatomaceous earth and molybdenum oxide are stirred in an organic solvent for 3-5 hours, and a membrane base mixture is obtained after drying. The membrane base mixture is then filled into a mold, compacted, and calcined at 450-600°C for 2-10 hours. The mold is demolded by natural cooling at room temperature, immersed in a water bath for rinsing for 1-3 hours, and then dried to obtain a high-strength composite membrane.

[0052] The composite membrane materials of Example 1, Comparative Example 1 and Comparative Example 2 are respectively loaded into the membrane filtration equipment, and the membrane filter is loaded with a sealing ring and 2.0Mpa pressure-maintaining wetted for 1h. Take 20kg batches of materials and store them in the liquid collecting tank of the membrane filter, and the batches of materials are controlled by the electromagnetic valve to enter the inside of the composite membrane through the tube layer at 10mL / min, and the acetic acid solution containing impurities is discharged from the shell layer. When the membrane flux is lower than 5LMH or after half an hour of operation, the trimellitic acid solids accumulated in the tube body are backwashed by nitrogen and pure water high pressure, and the batches of materials are tested for liquid phase concentration every 30min. After purification for 5-6h, high-purity trimellitic acid is put into a dehydration anhydride device to obtain trimellitic anhydride (the content of trimellitic acid is equivalent to the content of trimellitic anhydride).

[0053] The backwash liquid and the permeate were sampled and the concentration of trimellitic acid in the permeate was determined by HPLC. The retention rate (R%) was calculated using the following formula:

[0054] R=(C1-C2) / C1×100%

[0055] Wherein, C1 is the initial trimellitic acid concentration, and C2 is the trimellitic acid concentration in the permeate.

[0056] The calculation formula of membrane flux (F%) is as follows:

[0057] F=m / (S×T)×100%

[0058] Where m is the mass of the permeate and T is the permeation time.

[0059] It was determined that the purity of solid trimellitic acid obtained after purification by Zn / Ti@SMC-Y1 can reach 99.9%, and the yield is >97%. The measured data are as follows:

[0060] Table 1.1 Summary of membrane flux data

[0061] name Initial membrane flux / LMH Membrane flux / LMH after 10 backwashes Membrane flux / LMH after 20 backwashes SMC-Y1 12.1 11.9 10.8 SMC-Y2 11.0 10.9 6.6 Zn / Ti@SMC-Y1 12.2 12.2 12.2

[0062] Table 1.2 Membrane material interception rate after purification

[0063] name Initial interception rate / % Interception rate after 10 backwashing times / % Interception rate after 20 backwashing times / % SMC-Y1 36.8 35.2 33.6 SMC-Y2 32.5 26.9 16.5 Zn / Ti@SMC-Y1 61.3 60.9 60.1

[0064] Table 1.3 Trimellitic Acid Content after Purification

[0065] name Trimellitic acid / % Yield / % SMC-Y1 99.2 95.3 SMC-Y2 98.9 94.6 Zn / Ti@SMC-Y1 99.9 97.4

[0066] The results show that the mechanical properties of inorganic non-metallic membrane materials are significantly improved by tempering, and high-pressure recoil is not easy to damage the internal structure of the membrane material. The membrane separation material modified with the surface metal coating can better purify trimellitic acid, and the interception rate is more prominent than that of the membrane separation material without surface modification, and the yield is significantly improved. The anti-adhesion property of the surface coating makes it difficult for the accumulated solids to stick to the tube wall, and the membrane flux remains unchanged after repeated use.

[0067] Table 1.4Zn / Ti@SMC-Y1 purification data summary

[0068] Time / h Trimellitic acid / % Interception rate / % Membrane flux / LMH 0 95.2 5.2 12.1 0.5 96.4 27.8 12.2 1 97.8 46.4 12.3 1.5 98.6 59.6 12.2 2 99.2 60.7 12.0 2.5 99.7 60.9 12.2 3 99.8 60.5 12.1 3.5 99.9 60.8 11.9 4 99.9 60.2 12.2 4.5 99.9 60.1 12.1 5 99.9 60.1 12.2

[0069] The results show that Zn / Ti@SMC-Y1 reaches a maximum interception rate of 60.9% after 2.5 hours of filtration, and reaches a maximum purity of 99.9% of solid trimellitic acid obtained by evaporating the purified liquid after 3.5 hours of filtration, and remains stable during subsequent filtration operations. The tempered modification of the membrane material and the addition of rare earth metals enable the separation material to still be stable and efficient under high resistance conditions, and the surface metal coating modification optimizes the separation performance and anti-pollution ability of the membrane material.

[0070] Example 2

[0071] Referring to Example 1, "8 g ZnO powder and 45 g tetraisopropyl titanate" were used in step (2), and the rest was the same as in Example 1. The calculated yield was 97.3%, and the other measured data were as follows:

[0072] Table 2 Summary of purification data of Zn / Ti@SMC-Y1

[0073]

[0074]

[0075] Embodiments 3 to 7

[0076] On the basis of Example 1, the mass ratio of HEMA / metal nanoparticle polyester was changed to obtain the data listed in Table 3.

[0077] Table 3 Effect of the amount of surface metal coating on the separation performance of Zn / Ti@SMC-Y1

[0078]

[0079] The results show that the greater the amount of surface metal coating added, the higher the interception rate, but the thicker the coating, the greater the separation resistance, that is, the lower the flux. When the HEMA / metal nanoparticle polyester (m / m) is 1:1, the trimellitic acid content is the highest and the separation effect is the best. This ratio is not limited to these two substances, and the coating compounding agent can be replaced according to the actual working conditions or solvents.

[0080] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for purifying electronic grade trimellitic anhydride, characterized in that: The steps include: (1) Preparation of base mixture Silicon dioxide, molybdenum oxide and single crystal silicon are pre-ball-milled, cooled, and then activated carbon is added and calcined at high temperature in air, so that silicon dioxide, molybdenum oxide and single crystal silicon and activated carbon are crystallized at high temperature to form a crystal structure with nanopores. After the calcination, they are then calcined in air with an open flame to remove surface impurities and change the surface from black to grayish white, thereby obtaining Si-Mo / C particles, which are recorded as SMC particles. Then SMC particles, attapulgite, diatomaceous earth, magnesium oxide, 45 # The steel powder and the rare earth yttrium powder are mixed and ball-milled, and then vacuum ball-milled, and after the ball mill is cooled, a matrix powder is obtained; Then, the base powder is dissolved in triethylamine and dispersed evenly, polyvinylidene fluoride, polyethyl methacrylate, polyethylene glycol and trioctyl trimellitate or tetraoctyl pyromellitate are added, stirred thoroughly, and dried to obtain a base mixture; Preparation of Metal Nanoparticle Polyester Coating Materials Prepare KH-570 ethanol solution, add dimethylformamide as stabilizer, mix well and set aside; Then, ZnO powder and tetraisopropyl titanate are weighed in proportion and dissolved in deionized water, and azobisisobutyronitrile is added dropwise and nitrogen is sealed. After heating in a water bath and stirring, KH-570 ethanol solution is added dropwise. After the reaction is complete, glacial acetic acid or ammonia water is added dropwise to adjust the solution to neutrality, and the mixed liquid is then uniformly mixed with polyester resin to obtain a metal nanoparticle polyester coating material, which is sealed for later use; (3) Preparation of high-strength membrane separation materials reinforced with metal particles A mixture of hydroxyethyl methacrylate and the metal nanoparticle polyester coating material obtained in step (2) in a mass ratio of 1: (0.5-1.2) is evenly applied on the surface of the film mold, and then the base mixture obtained in step (1) is filled into the mold, and after pressure compaction, a temperature rise program is set to sinter and form, and after cooling, annealing treatment is performed, and demolding is performed at room temperature by natural cooling, immersing in a water bath for rinsing and then drying to obtain a metal particle reinforced high-strength composite film, which is recorded as Zn / Ti@SMC-Y1; (4) Purification of trimellitic anhydride A high-strength composite membrane reinforced with metal particles is installed in a filtering device and used as a filter material. The filtering device is also equipped with a high-pressure recoil device for nitrogen and pure water. When purifying trimellitic acid, a batch of semi-finished trimellitic acid products is filtered through the filtering device using intermittent operation. When the membrane flux decreases below an ideal value, the high-strength composite membrane reinforced with metal particles is regenerated by high-pressure recoil of nitrogen and pure water. After regeneration, filtration is continued until the trimellitic acid reaches a maximum purification accuracy. The purified trimellitic acid is placed in a dehydration anhydride dehydrator for dehydration to obtain trimellitic anhydride.

2. A method for purifying electronic grade trimellitic anhydride according to claim 1, characterized in that: In the step (1), the mass ratio of silicon dioxide, molybdenum oxide, single crystal silicon and activated carbon is (25-30): (0.5-2): (8-13): 35, and the ball milling time is 2 hours; the calcination temperature is 400-600° C., and the calcination time is 4-5 hours.

3. A method for purifying electronic grade trimellitic anhydride according to claim 1, characterized in that: The mass ratio of the SMC particles, attapulgite, diatomaceous earth, magnesium oxide, 45# steel powder and rare earth yttrium powder in the step (1) is (10-15): (60-100): (80-150): (20-40) (30-45): (0.5-1), and the ball milling time is 2 hours.

4. A method for purifying electronic grade trimellitic anhydride according to claim 1, characterized in that: The mass ratio of the matrix powder and triethylamine in step (1) is 2:5; the volume ratio of the polyvinylidene fluoride, polyethyl methacrylate, polyethylene glycol and trioctyl trimellitate or tetraoctyl pyromellitate is 5:2:1:(10-12).

5. The method for purifying electronic grade trimellitic anhydride according to claim 1, characterized in that: In step (2), the amount of ethanol used is 20 to 30 times the mass of KH-570, the amount of dimethylamide used is 1 to 3 times the mass of KH-570, the mass ratio of ZnO powder and tetraisopropyl titanate is (1 to 2): 5; the amount of azobisisobutyronitrile added is 0.3% of the total mass of the aqueous solution of ZnO powder and tetraisopropyl titanate; the constant temperature of the water bath is 30 to 45° C., and the stirring time is 5 to 6 hours; the amount of the polyester resin used is 10 to 15 times that of the mixed liquid.

6. The method for purifying electronic grade trimellitic anhydride according to claim 1, characterized in that: In step (3), the mold pressure is 20-30 MPa; the sintering process is vacuum sintering, the vacuum degree is 8-15 Pa, the heating rate is 30-45°C / min, the sintering temperature is 1000-1500°C; the annealing temperature is 400-600°C, and the holding time is 2-3h.

7. The method for purifying electronic grade trimellitic anhydride according to claim 1, characterized in that: In step (3), the water bath rinsing temperature is 20° C. and the rinsing time is 1 to 3 hours.

8. The method for purifying electronic grade trimellitic anhydride according to claim 1, characterized in that: The aqueous solution after high-pressure backwashing in step (4) can be circulated into the raw material kettle for repeated filtration.

Citation Information

Patent Citations

  • Method for reducing content of impurities in trimellitic anhydride

    CN102516212A

  • Method for promoting crystallization of trimellitic acid

    CN112110813A